2012
DOI: 10.1039/c1dt11212k
|View full text |Cite
|
Sign up to set email alerts
|

Magnetization, Mössbauer and isothermal dilatometric behavior of oxidized YBa(Co,Fe)4O7+δ

Abstract: Mössbauer spectroscopy and magnetization studies of YBaCo(4-x)Fe(x)O(7+δ) (x = 0-0.8) oxidized at 0.21 and 100 atm O(2), indicate an increasing role of penta-coordinated Co(3+) states when the oxygen content approaches 8-8.5 atoms per formula unit. Strong magnetic correlations are observed in YBaCo(4-x)Fe(x)O(8.5) from 2 K up to 55-70 K, whilst the average magnetic moment of Co(3+) is lower than that for δ ≤ 0.2, in correlation with the lower (57)Fe(3+) isomer shifts determined from Mössbauer spectra. The hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…The data on ceramic samples [8][9][10], results of theoretical calculations (triclinic cell of sym-metry P1, ~11600 atoms) [11], and the data on single crystals obtained in this study are indicative of many ways for implementing symmetry and unit-cell metric. Apparently, depending on the degree of saturation with oxygen, compounds may have different structures.…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations
“…The data on ceramic samples [8][9][10], results of theoretical calculations (triclinic cell of sym-metry P1, ~11600 atoms) [11], and the data on single crystals obtained in this study are indicative of many ways for implementing symmetry and unit-cell metric. Apparently, depending on the degree of saturation with oxygen, compounds may have different structures.…”
Section: Discussionmentioning
confidence: 66%
“…5c) and Со (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) in the cross section with z ≈ 0.25 (0.23-0.27) (Fig. 5d).…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…A single crystal Mössbauer study on YBaCo 3 FeO 7 revealed two spin freezing temperatures of T c1 = 590 K and T c2 = 50 K corresponding to the spin freezing at the Kagomé layers and triangular layers, respectively [32]. However, a Mössbauer study on powder compounds [YBaCo 4-x Fe x O 7+δ (x = 0-0.8) ] reported single spin freezing temperature ~ 70 K [33]. The present neutron diffraction study shows the onset of the magnetic ordering around 130 K for all compounds, however, with no observable change in the magnetic diffraction peak around T c2 .…”
Section: Ac Susceptibilitymentioning
confidence: 99%